The myosin and RhoGAP MYO9B influences osteocyte dendrite growth and responses to mechanical stimuli - Lee, Beth S.; Murray, Cynthia; Liu, Jie; Kim, Minji; Hwang, Min Sik; Yueh, Tina; Mansour, Myrna; Qamar, Sana; Agarwal, Gunjan; Kim, Do-Gyoon (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Myosin IXB (MYO9B) is an unconventional myosin with RhoGAP activity and thus is a regulator of actin cytoskeletal organization. MYO9B was previously shown to be necessary for skeletal growth and health and to play a role in actin-based functions of both osteoblasts and osteoclasts. However, its role in responses to mechanical stimulation of bone cells has not yet been described. Therefore, experiments were undertaken to determine the role of MYO9B in bone cell responses to mechanical stress both in vitro and in vivo.Methods: MYO9B expression was knocked down in osteoblast and osteocyte cell lines using RNA interference and the resulting cells were subjected to mechanical stresses including cyclic tensile strain, fluid shear stress, and plating on different substrates (no substrate vs monomeric or polymerized collagen type I). Osteocytic cells were also subjected to MYO9B regulation through Slit-Robo signaling. Further, wild-type or Myo9b -/-mice were subjected to a regimen of whole-body vibration (WBV) and changes in bone quality were assessed by micro-CT.Results: Unlike control cells, MYO9B-deficient osteoblastic cells subjected to uniaxial cyclic tensile strain were unable to orient their actin stress fibers perpendicular to the strain. Osteocytic cells in which MYO9B was knocked down exhibited elongated dendrites but were unable to respond normally to treatments that increase dendrite length such as fluid shear stress and Slit-Robo signaling. Osteocytic responses to mechanical stimuli were also found to be dependent on the polymerization state of collagen type I substrates. Wild-type mice responded to WBV with increased bone tissue mineral density values while Myo9b -/-mice responded with bone loss.Discussion: These results demonstrate that MYO9B plays a key role in mechanical stress-induced responses of bone cells in vitro and in vivo.